(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: : Dysphagia can cause significant morbidity and mortality, especially in older and paediatric populations. The study was undertaken to determine the demographic and clinico-pathological profile of the patients diagnosed with oesophageal dysphagia in a tertiary care hospital of Bangladesh. Methods: This cross-sectional study was conducted at the Department of Medicine & Gastroenterology in Sir Salimullah Medical College & Mitford Hospital over a period of 6 months, from March to August 2015. A total of 100 adult (aged ≥ 18 years) patients (respondents) of dysphagia of both sexes were included in the study. However, patients who dropped out before investigations being completed, or unconscious patients (as endoscopy cannot be done in unconscious patients) were excluded from the study. Result: The age distribution shows that patients were predominantly older (60%), male and rural resident. In terms of occupation, retired persons comprised the main bulk (38%). About half (49%) of the patients were middle-class and smoker. Presence of both solid and liquid food dysphagia was more or less common (44%), followed by solid food dysphagia alone (36%) and liquid food dysphagia alone (20%). A substantial proportion (78%) of patients presented with heart-burn as well. Probing the clue to dysphagia, some 7% of the patients gave history of ingesting chemical substances (either accidentally or as an attempt to suicide), 15% had history of taking steroid and 12% taking NSAIDs. History of radiation injury and history of ingesting foreign substances were rare. Over 60% of the respondents had co-morbid conditions like diabetes mellitus (28%), hypertension (23%), candidiasis (6%), lymphoma (3%). Clinical examination revealed 30% of the respondents nutritionally compromised (20% underweight and 10% overweight or obese). Nearly two-thirds (63%) were anaemiac with glossitis and koilonychia being present in 47 and 17% of the patients respectively. About one-third (32%) exhibited cervical lymphadenopathy. Of the 100 respondents, only 4 respondents were found with cardiomegaly, 4 with COPD, 2 with mediastinal widening. Endoscopy of upper GI tract showed 29% with ulceroproliferative lesion, 22% with multiple white patches in the whole length of oesophagus, 18% with stricture & narrowing of the oesophagus, 13% with malignant stricture & narrowing, 10% with proliferative lesion at mid oesophagus with narrowing of lumen and 8% malignant-looking ulcer with elevated margin in the lower oesophagus. Ba-swallow X-ray of oesophagus revealed 47 with filling defect in the lower oesophagus, 5 narrowing in the middle part of oesophagus and only 4 dilatations in the mid oesophagus. Twenty respondents had positive findings on USG of whole abdomen; of them, 10 had multiple solid tumors in liver. Others had hepatoma, mass in the epigastrium, cystitis, intraabdominal lymphadenopathy and splenomegaly. Based on symptoms, signs and laboratory findings, 42% were diagnosed as oesophagial carcinoma, 16% as drug-induced oesophageal ulcer and 11% as diabetes mellitus with oesophageal candidiasis. Conclusion: The most common cause of oesphageal dysphagia is carcinoma of oesophagus followed by drug-induced oesophageal ulcer and diabetes mellitus with oesophageal candidiasis. To reduce morbidity and mortality of various etiologies leading to dysphagia, prompt and early diagnosis is essential. Ibrahim Card Med J 2022; 12 (1): 40-45